Opodatkowanie dochodu a decyzje inwestycyjne przedsiębiorstw w świetle celów działalności gospodarczej - Adamczyk, Adam (Corporate Income Taxation versus Investment Decisions of Enterprises in the Light of Economic Activity Aims, 2006)
Empirical study of the relation between investment and corporate income taxation needs to be preceded by analysis of investment theories. These theories take different assumptions concerning the aim of the firm. The goal of the article is to show how assumptions concerning the aim of the firm can influence relation between corporate income taxation and investment. Thanks to it, it will be possible to indicate how relation between corporate taxation and investment should be examined in different types of firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 15-24